ETHICAL ISSUES IN ONLINE ADVERTISING AND ITS IMPACT ON CONSUMER BUYING BEHAVIOR - Nabi, Ghulam; Khan, Muhammad Kamran; Akram, Sabahat; Shafi, Maria; Khan, Muhammad Taimur; Qasim, Ghosia; Khan, Azhar (The journal of contemporary issues in business and government, 2020)
Online advertising is increasing day by day for trapping consumer’s attractions towards their products and services.This study aims to reveal the consumer perception towards the ethics in online advertising. Unverified claims, ads for social cause and surrogate ads these are the three factors that affecting consumer buying behavior (CBB) consider particularly this study.Data is collected by a modified questionnaire five point Likert scales was administered to a sample size of 223 students who were enrolled in different universities. This study also reveals that whether consumers are care about ethical purchase or not. Surrogate advertising is now considering an important trend in the field of advertising. The findings show that ad for social cause, surrogate ads and unverified claims have an impact on consumer buying behavior (CBB) and also explain the value of truth, social responsibility and consider human dignity in advertising.Further work is needed to explore the other factors and understand the possible effect of those factors on consumer buying behavior (CBB).